PENGARUH PENGERASAN MATA GERGAJI TERHADAP BEBERAPA SIFAT PENGGERGAJIAN - Osly Rachman; Jamal Balfas (Jurnal Penelitian Hasil Hutan, 1988)
Fifteen  mahogany and  six  agathis logs in fresh  cut  condition were sawn  into  boards  by a  band saw  machine.  Each wood  species  was  sawn  using  three  saw blades  with  different  cutting   edge  hardness  i.e. hand  swaging,  alternate  stellite .  tipping  and  full  stellite   tipping.   Sawing  properties recorded include  power consumption,  cutting   rate  and  sawing  productivity    for each  wood  species and cutting  edge hardness.The  results of  study   showed   that  wood  species  had no significant  difference   in terms  of power   consumption   and cutting  rate.  Meanwhile, sawing productivity   of agathis was higher than mahogany.Furthermore, the cutting  edge hardnes had significant  effect on sawing properties. It  is found that the saw blade with alternate stellite tipping reduced power consumption, and  increased  the  cutting rate and productivity.